Cleo ebook : the cat who mended a family. - Brown, Helen (2010)
The Beloved #1 International Bestseller Tenth Anniversary Edition "We're just going to look. " Helen Brown had no intention of adopting a pet when she brought her young sons to visit a friend's new kittens. But the runt of the litter was irresistible, with her overlarge ears and dainty chin. When Cleo was delivered weeks later, she had no way of knowing that her new family had just been hit by an unthinkable tragedy. Helen was sure she couldn't keep her—until she saw something she thought had vanished from earth forever: her son's smile. The reckless, rambunctious kitten stayed. Through happiness and heartbreak, changes and new beginnings, Cleo was the glue that affectionately held Helen's family together. Rich in wisdom, wit, heart, and healing, here is the story of a cat with an extraordinary gift for knowing just where she was needed most. With a New Afterword by the Author "A remarkable memoir . . . Helen Brown opened my heart." —Beth Hoffman, New York Times bestselling author "An absolute must." —Cat World